2012
DOI: 10.5194/hess-16-4303-2012
|View full text |Cite
|
Sign up to set email alerts
|

Coupled daily streamflow and water temperature modelling in large river basins

Abstract: Abstract. Realistic estimates of daily streamflow and water temperature are required for effective management of water resources (e.g. for electricity and drinking water production) and freshwater ecosystems. Although hydrological and process-based water temperature modelling approaches have been successfully applied to small catchments and short time periods, much less work has been done at large spatial and temporal scales. We present a physically based modelling framework for daily river discharge and water… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(85 citation statements)
references
References 55 publications
4
81
0
Order By: Relevance
“…For example, the variations of temperature resulting from the fluctuations in discharge can be better resolved (e.g. van Vliet et al, 2012;Null et al, 2013). The use of both discharge and temperature measurement data to calibrate the model has also been shown by Comola et al (2015) to improve the quality of the simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the variations of temperature resulting from the fluctuations in discharge can be better resolved (e.g. van Vliet et al, 2012;Null et al, 2013). The use of both discharge and temperature measurement data to calibrate the model has also been shown by Comola et al (2015) to improve the quality of the simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 13 semi-distributed coupled models listed in Table 1, only 1 was specifically developed for mountainous environments (MacDonald et al, 2014). The other ones were either tailored to large-scale applications (Morrison et al, 2002;Ferrari et al, 2007;van Vliet et al, 2012;van Beek et al, 2012;Null et al, 2013) or aimed at being used over low-altitude catchments (e.g. Sullivan et al, 1990;Chen et al, 1998;Haag and Luce, 2008), except for the model of Sun et al (2015) which has been tested over Alpine watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…Textbox 1 specifies the hydrological-water temperature modeling framework used in this study. The performance of the modeling framework for daily streamflow and water temperature simulations has previously been evaluated by van Vliet et al [44], and shows a realistic representation of the observed water temperature conditions for the Rhine basin. For details about the application of this framework under the climate in the future, we refer to van Vliet et al [45].…”
Section: Step 4: Adaptation Turning Pointsmentioning
confidence: 99%
“…In the authors' previous studies , it was found that the TDG dissipation process is quantitatively different from the reaeration process of DO. Some biological studies also indicate that the supersaturated TDG is more harmful to the fishes than the supersaturated DO (Rucker, 1976). For these reasons, TDG is chosen as the key variable to study the eco-environmental regulations for mitigating the conflict between dam spilling and fish protection in the paper.…”
Section: The Previous Studiesmentioning
confidence: 99%
“…An optimized regulation policy for Bala Reservoir is proposed based on the numerical results. Politano (2009), Urban et al (2008, and Fu et al (2010) have developed unsteady two-phase threedimensional models to calculate the TDG downstream evolution of spillways. The accuracy is satisfied in their simulations.…”
Section: Objectivementioning
confidence: 99%